2017
DOI: 10.3389/fimmu.2017.00288
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Pathway of Complement Activation Is Associated with Vulnerability of Atherosclerotic Plaques

Abstract: Inflammatory mechanisms may be involved in atherosclerotic plaque rupture. By using a novel histology-based method to quantify plaque instability here, we assess whether lectin pathway (LP) of complement activation, a major inflammation arm, could represent an index of plaque instability. Plaques from 42 consecutive patients undergoing carotid endarterectomy were stained with hematoxylin-eosin and the lipid core, cholesterol clefts, hemorrhagic content, thickness of tunica media, and intima, including or not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 53 publications
0
33
0
4
Order By: Relevance
“…5b). The in vitro assay using acBSA-coated plates, which measures LP activation through ficolins, 18 did not show any difference among the genotypes (Fig. 5c).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…5b). The in vitro assay using acBSA-coated plates, which measures LP activation through ficolins, 18 did not show any difference among the genotypes (Fig. 5c).…”
Section: Resultsmentioning
confidence: 91%
“…We tested the activation of the LP in mouse plasma (pools from mice belonging to the same experimental group) using an in vitro assay 17 with mannan-coated plates, which measures LP activation through MBL. 18 There was no LP activation in MBL −/− and MBL-A −/− ischemic mice, whereas the LP remained active in Fig. 1 Neuroscore and ischemic volume after 48 h of reperfusion in MBL −/− , MBL-A −/− , and MBL-C −/− mice.…”
Section: Resultsmentioning
confidence: 92%
“…Hertle et al raised a conclusion from a large-sample cohort that the excessive AP activation would promote poor cardiovascular outcomes [5]. Fumaqalli et al found high expressions of Ficolins and mannose-binding lectin in plaques' necrotic core and tunica media of patients with severe coronary heart disease [6]. Therefore, determination of the exact role of each complement pathway and corresponding components in a specific heart disease will be much helpful to deeply understand the mechanisms of the diseases and provide valid and targeted therapeutic intervention to particular patients.…”
Section: Introductionmentioning
confidence: 99%
“…Já o Rugonfalvi-Kiss et al64 observaram que em 123 pacientes que foram submetidos a endarterectomia de carótida e foram acompanhados por eco-dopplergrafia de carótidas, a recorrência de estenose teve associação com altas concentrações de MBL no soro. Berger et al65 estudando pacientes com transplante simultâneo de pâncreas e rim demonstraram que há associação dos níveis de MBL > 400 ng/mL com pior sobrevida do enxerto e levantaram a hipótese de que a MBL contribui para a patogênese da lesão vascular induzida por inflamação, tanto nos vasos dos órgãos transplantados como nos vasos do indivíduo receptor.Assim, é provável que a MBL possua um duplo papel na DAC podendo promover e proteger contra inflamação, dependendo do cenário fisiopatológico no interior da parede do vaso e de que um equilíbrio bem ajustado é o que determina se o complemento é uma vantagem ou desvantagem na DAC 66. 1.3.…”
unclassified
“…Os autores analisaram as placas de ateroma e as categorizaram pelas características morfológicas associadas à instabilidade da placa 147 , tais como: conteúdo hemorrágico e de colesterol, a área de núcleo lipídico, espessura total da túnica e conteúdo infiltrativo vascular. Eles mostraram a presença da MBL no núcleo necrótico e na camada média da túnica contribuindo para a instabilidade da placa de ateroma 66. Portanto, os níveis de MBL podem ser possíveis sinalizadores de instabilidade da placa aterosclerótica.…”
unclassified